Modelo de gestión de abastecimiento para el mejoramiento del área de compras de la empresa soluciones institucionales del llano (SIDELL S.A.S.) (2022)
The objective of this degree work is to propose a supply management model in the purchasing area for organizational and productive strengthening in the company Soluciones Institucionales del Llano S.A.S. With the purpose of improving the supply chain as an integral organizational axis in a complete and practical way, considering the importance of the role of the purchasing and supplier management area.